2020
DOI: 10.1101/2020.02.24.963686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting TUG score from gait characteristics with video analysis and machine learning

Abstract: Fall is a leading cause of death which suffers the elderly and society. Timed Up and Go (TUG) test is a common tool for fall risk assessment. In this paper, we propose a method for predicting TUG score from gait characteristics extracted from video with computer vision and machine learning technologies. First, 3D pose is estimated from video captured with 2D and 3D cameras during human motion and then a group of gait characteristics are computed from 3D pose series. After that, copula entropy is used to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Specifically, they found that all are distinguishable in TUG, the Berg balance scale (BBS), and the combined TUG and the short-form Berg balance scale (SFBBS), indicating that MSE can effectively classify the participants of these clinical tests using behavioral actions. Jian et al (2020) [ 17 ] also employed entropy with video analysis and machine learning to predict the TUG score from gait characteristics. Their results showed that copula entropy is used to select the characteristics that are mainly related to the TUG score.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, they found that all are distinguishable in TUG, the Berg balance scale (BBS), and the combined TUG and the short-form Berg balance scale (SFBBS), indicating that MSE can effectively classify the participants of these clinical tests using behavioral actions. Jian et al (2020) [ 17 ] also employed entropy with video analysis and machine learning to predict the TUG score from gait characteristics. Their results showed that copula entropy is used to select the characteristics that are mainly related to the TUG score.…”
Section: Introductionmentioning
confidence: 99%
“…Because the TUG test consists of relatively simple activities, it can be easily distinguished using low-dimensional features, such as human posture detected by body keypoints [18]. Therefore, previous studies investigated various types of input data to obtain efficient results with subtask segmentation [3,4,18,22,23,28,35,37,41] or fall risk prediction [25,42]. We summarize these in Table A1 in the Appendix A.…”
Section: Input Comparison Studymentioning
confidence: 99%
“…These findings motivated us to speculate that similar locations might be better than other locations in the TUG subtask segmentation task by using a lower resolution of RGB-D than the IMU. Previous studies using RGB or RGB-D cameras used complete skeleton data spread throughout the body as inputs to ANN models or rules [18,22,42]. We hypothesized that the input(s) only from the proximal joints, for example, center of gravity (COG) movement or head motion, and not with all 32 skeleton joints, should be sufficient for classifying TUG subtasks.…”
Section: Input Comparison Studymentioning
confidence: 99%